Board characteristics and financial performance: Evidence from Indian cooperative banks. Issue 2 (December 2018) - Ghosh, Saibal; Ansari, Jugnu
Highlights: Employs data on Indian urban cooperative banks to analyze the interlinkage between governance and performance. Board size does not affect performance, although there is a perceptible impact of gender diversity on performance. The results differ across high- and low-districts and across large and small boards. Highlights the need for a careful re-look at board composition and diversity in the context of cooperative banks. Abstract: The paper examines the association between financial performance and boards of urban cooperative banks in India. Utilizing cross-sectional data on 1263 banks for 2012, the findings indicate that, after controlling for various factors, board size does not affect performance. Further disaggregation suggests that board size matter in high-income districts, although bigger boards per se are less conducive to performance, reflecting the challenges of free-riding problems and time-consuming decision making process among board members. In terms of implications, the results suggest that board sizes need to be carefully tailored, taking on board regional and economic considerations.